Diagnóstico de la producción de semilla de buena calidad para el pequeño agricultor. - Instituto Colombiano Agropecuario, Bogotá (Colombia) (Instituto Colombiano Agropecuario - ICA, 1983)
Fríjol-Phaseolus vulgaris